1982
DOI: 10.1002/jpln.19821450505
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Phosphate Dissolving Bacteria on the Efficiency of Superphosphate in a Calcareous Soil Cultivated with Vicia faba

Abstract: In a pot experiment with Vicia faba grown in a calcareous soil and fertilized with three rates on superphosphate, inoculation with phosphate dissolving bacteria (PDB) increased P‐uptake and dry weight. The effect of inoculation exceeded that of the fertilization with half of the usual rate. Dry weight and P‐uptake of plants grown in inoculated soils receiving one half of the usual rate of superphosphate were higher than those for plants grown in pots receiving the usual rate of superphosphate in the absence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The soils were therefore unsterilized, the recommended fertilizers applied and the microbial strains were only evaluated for their capacity to enhance crop yields. Experiments carried out in agriculturally advanced countries using culture suspensions of phosphorus-solubilizing organisms have demonstrated that they can have a significant effect on the mobilization of soil phosphates and increase crop yields (Khalafallah et al, 1982;Barea and Azcon-Agnilar, 1982;Monib et al, 1984;Fernandez et al, 1985;Badr et al, 1986;Piccini and Azoon, 1987). These results and those from our experiment show that bio-fertilization with phospho-microbes has considerable potential.…”
Section: Resultsmentioning
confidence: 99%
“…The soils were therefore unsterilized, the recommended fertilizers applied and the microbial strains were only evaluated for their capacity to enhance crop yields. Experiments carried out in agriculturally advanced countries using culture suspensions of phosphorus-solubilizing organisms have demonstrated that they can have a significant effect on the mobilization of soil phosphates and increase crop yields (Khalafallah et al, 1982;Barea and Azcon-Agnilar, 1982;Monib et al, 1984;Fernandez et al, 1985;Badr et al, 1986;Piccini and Azoon, 1987). These results and those from our experiment show that bio-fertilization with phospho-microbes has considerable potential.…”
Section: Resultsmentioning
confidence: 99%
“…Seed or soil inoculation with phosphobacteria was reported to improve the yield and nutrient uptake of various crops (Khalafallah, 1982). The favourable effect of the inoculants on plant growth and nutrient uptake was due to the improved phosphate nutrition and production of growth promoting substances by PSM (Barea et al, 1976;Sattar and Gaur, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the reason that these microorganisms utilize and adapt certain mechanisms which directly contribute and improve plant growth and yield. Inoculatin Vicia faba plants with phosphate solubilizing bacteria, Khalafallah et al (1982) indicated that phosphorus fertilization was reduced by 50% with inoculation. The plants applied with half dose of fertilizer resulted in similar dry mass to that plant applied with 100% of fertilizers.…”
Section: Dry Matter Partitioningmentioning
confidence: 99%